TFAP2A promotes NSCLC malignant progression by enhancing AOC1 transcription - Xiang Miao; Hongzhen Zheng; Huimin Mo; Jing Chang; Qin Jia; Hai Zhou (Hereditas)
Abstract Background Non-small cell lung cancer (NSCLC) has high mortality, and patients show variable outcomes and drug responses. Amine oxidase copper-containing 1 (AOC1) is considered an oncogene in many types of tumors. Transcription factor AP-2 alpha (TFAP2A) can affect a variety of biological processes and play a crucial role in driving tumorigenesis and tumor development. Consequently, this work is designed to delve into the effects of AOC1 and TFAP2A on NSCLC progression. Methods Bioinformatics analysis was employed to analyze AOC1 and TFAP2A expression in the TNMplot database and the survival significance of high- or low-expression of AOC1 in NSCLC patients. Quantitative real-time polymerase chain reaction (RT-qPCR) and western blot were implemented to assay the mRNA and protein expression levels of genes. Cell proliferation, migration, and apoptosis were detected using 5-ethynyl-2’-deoxyuridine (EdU), wound healing, and flow cytometry, respectively. In addition, mitochondrial membrane potential and reactive oxygen species (ROS) were examined using JC-1 and ROS detection kits. The macrophage M2 polarization was tested via flow cytometry. The construction of subcutaneous transplanted tumors in nude mice confirmed the effect of AOC1 in vivo. In order to discern the upstream regulatory mechanisms, the JASPAR database was utilized to predict the transcription factors and binding sites associated with AOC1. Chromatin immunoprecipitation (CHIP) and luciferase reporter gene assays were performed to solidify the binding relationship between AOC1 and TFAP2A. Results AOC1 and TFAP2A levels were increased in NSCLC tumor tissues and cell lines (A-549 and NCI-H1299). AOC1 knockdown inhibited NSCLC cell proliferation, migration, M2 macrophage polarization, and mitochondrial membrane potential, and facilitated cell apoptosis and ROS. In vivo, sh-AOC1 suppressed NSCLC tumor growth. Furthermore, TFAP2A facilitated AOC1 expression via transcriptional regulation in NSCLC. Mechanically, TFAP2A promoted NSCLC progression via facilitating AOC1 expression. Conclusions Silencing TFAP2A inhibits NSCLC progression via regulating AOC1 transcription. Hence, AOC1/TFAP2A may be a feasible therapeutic target for NSCLC. Graphical Abstract